2001
DOI: 10.1007/pl00007986
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis of movement strategies in human forward trunk bending. I. Modeling

Abstract: Two behavioral goals are achieved simultaneously during forward trunk bending in humans: the bending movement per se and equilibrium maintenance. The objective of the present study was to understand how the two goals are achieved by using a biomechanical model of this task. Since keeping the center of pressure inside the support area is a crucial condition for equilibrium maintenance during the movement, we decided to model an extreme case, called "optimal bending", in which the movement is performed without a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
106
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(122 citation statements)
references
References 0 publications
14
106
2
Order By: Relevance
“…The resulting body configurations in these two panels look similar to those resulting from the eigenmovements proposed by Alexandrov and his colleagues (2001), based on decomposition of the equation of motion of a three-link inverted pendulum in two dimensions. In particular, the kinematics induced by activation of M 1 or M 2 +M 3 (see Figure 12A) is similar to the hip eigenmovement (H-eigenmovement) reported by Alexandrov et al (2001), i.e. hip flexion combined with ankle plantarflexion (cf.…”
Section: Composition Of Muscle Modessupporting
confidence: 71%
See 1 more Smart Citation
“…The resulting body configurations in these two panels look similar to those resulting from the eigenmovements proposed by Alexandrov and his colleagues (2001), based on decomposition of the equation of motion of a three-link inverted pendulum in two dimensions. In particular, the kinematics induced by activation of M 1 or M 2 +M 3 (see Figure 12A) is similar to the hip eigenmovement (H-eigenmovement) reported by Alexandrov et al (2001), i.e. hip flexion combined with ankle plantarflexion (cf.…”
Section: Composition Of Muscle Modessupporting
confidence: 71%
“…"ankle strategy", Horak and Nashner 1986). Alexandrov et al (2001) showed that, during the same translation of the center of mass (COM; 1 cm in 500 ms), the A-eigenmovement was associated with an almost four times larger COP excursion than the H-eigenmovement (6.5 cm as compared to 1.7 cm). On the other hand, due to the difference in the inertial properties of the body segments (see Alexandrov et al, 2001), the A-eigenmovement is more efficient for slow motions, while the H-eigenmovement is more efficient for fast COM motions (see also Horak and Nashner, 1986;Runge et al, 1999).…”
Section: Composition Of Muscle Modesmentioning
confidence: 99%
“…Eigenvectors and eigenvalues were used to describe independent combinations of joint movements, defined by principle component analysis (Kuo et al, 1998;Alexandrov et al, 2001a;Hsu et al, 2007). From the covariance matrix of the ankle and hip angle, the first component may be interpreted as double-inverted pendulum behaviour and quantifies the amount of hip strategy.…”
Section: Root Mean Square and Covariance Descriptormentioning
confidence: 99%
“…To maintain standing balance in various situations, postural responses must adapt with task, magnitude and type of external disturbance (Alexandrov et al, 2001b;Park et al, 2004;Kim et al, 2012). Studies in the upper and lower extremities showed that the neuromuscular controller also adapted when external force fields were applied (Shadmehr and Mussa-Ivaldi, 1994;Burdet et al, 2001;Noël et al, 2008;van Asseldonk et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation